Retention of Postocular Visible Implant Elastomer in Two Sizes of Adult Brown Trout and Rainbow Trout. (14th July 2021) - Bushon, Amanda M.; Rash, Jacob M.
Abstract: Retention of visible implant elastomer (VIE) was assessed during an evaluation of put‐grow‐and‐take Brown Trout Salmo trutta and Rainbow Trout Oncorhynchus mykiss stockings in Apalachia Reservoir, North Carolina. Visible implant elastomer was injected in the postocular adipose tissue of two sizes (approximately 254 [small] and 356 [large] mm TL) of Brown Trout and Rainbow Trout in November 2012–2015. Each year, 1, 000 large and 1, 500 small trout of each species were marked with VIE. Mark retention was assessed after 30 d in a hatchery and during poststocking collection events in Apalachia Reservoir. The recaptured trout were examined for VIE marks during annual spring electrofishing, fall gill‐net samples, and a year‐long creel survey. The 30‐d VIE retention rate for all trout and all years was 99.9%. Following stocking, both sizes of Rainbow Trout were collected up to 17 months after marking and VIE retention was 100%. Large and small Brown Trout were collected up to 33 and 34 months after marking, and the VIE retention rates were 100% and 99.3%, respectively. This study found visible implant elastomer to be an effective and simple batch mark that remained visible on Rainbow Trout for up to 17 months and Brown Trout for up to 34 months postmarking in the wild.